Undergraduate hospitality students’ pre-entry career expectations - Dale, Rebecca A. (Kansas State University, 2013)
The psychological contract is comprised of the perceived obligations between two parties, such as an employee and an employer. When an individual joins an organization, the employee has a specific set of personal needs to be satisfied, which will be fulfilled by the psychological contract. Research has historically focused on the consequences of the psychological contract violations. The antecedents and the formation of the psychological contract are less known. Two types of psychological contracts exist: transactional and relational. In past research, undergraduate students enrolled in hospitality programs have indicated that transactional contracts are most important. Research has been limited on undergraduate hospitality students and their expectations of the workplace, thus the purpose of this study was to explore undergraduate hospitality students’ pre-entry career expectations. An online survey was distributed to undergraduate hospitality students at universities in the United States. Students highly ranked a safe work environment (8.7 ± 2.5), resources (7.8 ± 3.0) and equipment (7.4 ± 3.2) to do their jobs, training (8.2 ± 2.9), and job security (7.7 ± 3.1). The least important and expected items were work schedules with limited nights and weekends (2.5 ± 4.3) and working 40 or less hours per week (2.5 ± 4.1). The number of college credit hours completed and amount of work experience had the largest effects between expectations. Results of this study will assist hospitality educators in preparing students for post-graduation employment and offer industry recruiters insight into what expectations are important to new hospitality graduates.
Keywords: Psychological contract; Pre-entry career expectation; Undergraduate hospitality students; Higher Education (0745); Management (0454); Organizational Behavior (0703)